Review of the pharmaceutical treatment outcome in cases of complicated systemic lupus erythematosus with aplastic anemia (Journal of Pharmaceutical Negative Results, 2012)
There are few reports about the presentation of systemiclupus erythematosus (SLE) with aplastic anemia (AA). Allof them have reported obscurant cases that have beenthreatened with routine or new immunosuppressive agents.It seems that it is necessary to analyze these cases for a finalconclusion, although previous reports have been concludedwith regard to their findings and some of them have rarelyprovided a review.[1]